1999
DOI: 10.1046/j.1365-2044.1999.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised double‐blind comparison of morphine vs. a morphine–alfentanil combination for patient‐controlled analgesia

Abstract: In a randomised, double-blind study, we compared a combination of morphine and alfentanil with morphine alone for patient-controlled analgesia (PCA) after Caesarean section under spinal anaesthesia. After surgery, patients were randomly allocated to receive PCA with a bolus dose of either morphine 0.75 mg plus alfentanil 0.125 mg (Group MA, n = 40) or morphine 1.5 mg alone (Group M, n = 37) with a lockout interval of 8 min and no hourly dose limit. Clinical assessments were made in the first 24 h, after which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The first study examined a combination of morphine and alfentanil for PCA use after caesarian section. It found that patients who received the combination reported faster onset of analgesia after a PCA bolus when compared with a morphine alone PCA group 13 . Similar to our study, this advantage was not reflected in the visual analog scale pain scores.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The first study examined a combination of morphine and alfentanil for PCA use after caesarian section. It found that patients who received the combination reported faster onset of analgesia after a PCA bolus when compared with a morphine alone PCA group 13 . Similar to our study, this advantage was not reflected in the visual analog scale pain scores.…”
Section: Discussionsupporting
confidence: 86%
“…There are only 2 studies looking at pure agonist opioid mixtures for PCA in the literatue 13,14 . The first study examined a combination of morphine and alfentanil for PCA use after caesarian section.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the efficacy of morphine alone and an alfentanil−morphine mixture in the setting of patient‐controlled analgesia (PCA), finding no difference in reported pain scores over a 24‐h period [7]. Although the timing of recording pain scores used would not be expected to be particularly sensitive at detecting onset of analgesia, patients in the mixture group reported that they felt that the onset of pain relief was ‘fast’ more frequently than those in the morphine alone group.…”
Section: Discussionmentioning
confidence: 99%